Corrosion Performance of Embedded Steel in Fly Ash Geopolymer Concrete by Impressed Voltage Method - Olivia, Monita; Nikraz, Hamid (CRC Press/Baklema, 2010)
The present paper covers a study of the corrosion performance of embedded steel in fly ash geopolymer concrete by an accelerated corrosion test set up. Concrete specimens were exposed to a constant impressed voltage of 5V and 30V. Two optimized fly ash geopolymer concrete mixtures were compared with a control mix (OPC concrete) at an equivalent strength grade. Alkalinity reduction by phenolphthalein spray, chloride penetration by AgNO3 spray and half cell potential measurement were also investigated. The accele-rated corrosion test was carried out for 28 days. Results indicate that the geopolymer concrete displayed a smaller recorded current and higher electrical resistance than the corresponding control mix. Small cracks were observed in the fly ash geopolymer samples. It can be concluded that the fly ash geopolymer concrete had good corrosion performance and yielded longer time to failure than the OPC concrete.